Fundamental Motor Skills in Identifying Differences in Performance level between Students and Athletes Ages 10-12 years - Rovena Elmazi; Florian Miftari (Nicolaus Copernicus University in Toruń, 2020)
Fundamental motor skills that are developed during childhood are considered to be the building blocks for sport-specific movement patterns and are typically the focus of physical development programs for children, to develop gross motor skills from early childhood. Specifically, it has been shown that within a sport-specific environment, fundamental motor skills can separate children with potential for sport success. This is because gross motor skills underpin the development of the more specific sport skills that will likely be required for future sport success. The study aimed to assess fundamental motor skills in identifying differences in performance levels between students and athletes aged 10-12 years living in Albania, and further examine the indicators obtained in order to study how these two groups of children compare to each other. The data gathered through this study are indispensable in revealing the level of obesity, physical and technical capacities and identifying talented athletes. 641 students coming from the primary and secondary school systems and 410 athletes were subjected to standard anthropometric measurements (weight/height/BMI), standard physical fitness tests (push-up, abdominal press high jump, long jump, horizontal stretch, 30m dash, shuttle run 112 m) and technical measurements (Bridling, passing boll, Moving in defence and shooting) Based on BMI standards for students and athletes of this age group, it can be observed that athletes demonstrate a growth in body mass, even the physical fitness and technical indicators tested  speak for a bigger development of athletes . Therefore, testing procedures should be expanded from only subjective measures of players' abilities and objective tests of specific conditioning capacities to the objective assessments of technical capacities connected to the motor skills of individuals. This could then be used to select children at an age when the goal is to identify those talented in basketball.